Why do acute healthcare staff engage in unprofessional behaviours towards each other and how can these behaviours be reduced? A realist review protocol - Ruth Abrams; Aled Jones; Johanna Westbrook; Jill Maben; Russell Mannion; Judy M Wright; Mark Pearson; Justin Avery Aunger (BMJ Open)
Introduction Unprofessional behaviours encompass many behaviours including bullying, harassment and microaggressions. These behaviours between healthcare staff are problematic; they affect people’s ability to work, to feel psychologically safe at work and speak up and to deliver safe care to patients. Almost a fifth of UK National Health Service staff experience unprofessional behaviours in the workplace, with higher incidence in acute care settings and for staff from minority backgrounds. Existing analyses have investigated the effectiveness of strategies to reduce these behaviours. We seek to go beyond these, to understand the range and causes of such behaviours, their negative effects and how mitigation strategies may work, in which contexts and for whom.Methods and analysis This study uses a realist review methodology with stakeholder input comprising a number of iterative steps: (1) formulating initial programme theories drawing on informal literature searches and literature already known to the study team, (2) performing systematic and purposive searches for grey and peer-reviewed literature on Embase, CINAHL and MEDLINE databases as well as Google and Google Scholar, (3) selecting appropriate documents while considering rigour and relevance, (4) extracting data, (5) and synthesising and (6) refining the programme theories by testing the theories against the newly identified literature.Ethics and dissemination Ethical review is not required as this study is a secondary research. An impact strategy has been developed which includes working closely with key stakeholders throughout the project. Step 7 of our project will develop pragmatic resources for managers and professionals, tailoring contextually-sensitive strategies to reduce unprofessional behaviours, identifying what works for which groups. We will be guided by the ‘Evidence Integration Triangle’ to implement the best strategies to reduce unprofessional behaviours in given contexts. Dissemination will occur through presentation at conferences, innovative methods (cartoons, videos, animations and/or interactive performances) and peer-reviewed journals.PROSPERO registration number CRD42021255490.